STUDI NASKAH FIKIH MELAYU (RISALAH IS’AF AL RAGHIBIN FI ‘ILMI AL FARAIDH) KARYA JAD AHMAD MUBARAK - Wahidah Wahidah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2019)
Jad Ahmad Mubarak is a title that was deliberately chosen by the composer of Risalah Is'af al Raghibin fi ‘Ilmi al Faraidh. The name is indeed not found in any one site, but the teacher and caretaker of Al Mursyidul Amin Islamic Boarding School has experience and deep understanding on Fiqh Mawarits. This handwritten work is not widely known by the Banjar Muslim community. So, this paper discusses the "perwajahan(faces)" and characteristics of this work. In fact, the work on the science of faraidh has raised opinions regarding "the meaning of parallels between men and women in the context of the ashobah". The other findings are the composition of his writing contains a number of chapters consisting of 41 shahifahs. Every description is preceded by Arabic poetry, although not entirely translated into Malay Arabic. As part of the contents of the book, the author also added his discussion about Jadwal al Hujbi. The content has a complete material content like the book of Faraidh, all of which are presented in illustrative examples of each case.Jad Ahmad Mubarak merupakan gelar yang sengaja dipilih oleh penyusun Risalah Is’af al Raghibin fi ‘Ilmi al Faraidh. Namanya memang tidak dijumpai dalam satu situs sekalipun, namun pengajar dan pengasuh Pondok Pesantren Al Mursyidul Amin ini memiliki pengalaman dan pemahaman yang dalam mengenai fikih mawarits. Karya dengan tulisan tangan ini, tidak banyak diketahui oleh masyarakat Muslim Banjar. Tulisan ini membahas “perwajahan” dan karakteristik risalah ini. Risalah tentang ilmu faraidh ini telah memunculkan pendapat terkait “makna kesejajaran antara laki-laki dan perempuan dalam konteks ashobah”. Adapun temuan lainnya adalah komposisi tulisannya memuat sejumlah bab yang terdiri 41 shahifah. Setiap uraian didahului dengan syair-syair berbahasa Arab, meskipun tidak seluruhnya diterjemahkan ke dalam bahasa Arab Melayu. Sebagai kelengkapan isi Risalah, pengarangnya juga menambahkan bahasannya mengenai Jadwal al Hujbi. Muatan materi yang lengkap layaknya kitab faraidh, semuanya disajikan dengan illustrasi contoh-contoh setiap kasus.